Fitotoxicidade do extrato etanólico de folhas de nabo (Raphanus sativus L.) - Silva, Regildo M. G. [UNESP]; Brante, Rogério T. [UNESP]; Santos, Valter H. M. [UNESP]; Mecina, Gustavo F. [UNESP]; Silva, Luciana P. (My University, 2014)
The study of allelopathic activity has been aim of research that evaluates mainly species used in green fertilization. Raphanus sativus L. stands out among these species, because it shows high capacity for nutrient recycling, specially nitrogen and phosphorus, what makes it an advantageous cover plant in crop rotation systems. Considering the exposed, the present study had as objective the evaluation of the allelopathic and phytotoxic potentials of different concentrations of the R. sativus leaves ethanolic extract by mean of seeds germination analyses and development of lettuce seedlings, evaluating the phytotoxicity by determination of the mitotic index of lettuce root cells, realizing the phytochemical profile and investigating the antioxidant activity. It was possible to verify that the R. sativus extract interferes in the germination index, decreasing the germinability (5 mg.mL-1 = 9.84%; 10 mg.mL-1 = 11.91% and 20 mg.mL-1= 57.51%). In the lettuce seedlings growth, the extract of this species affected the roots and hypocotyls growth. It was possible to observe phenols and total flavonoids in the extract for the concentration of 1000μg.mL-1(161mg and 83.57 mg, respectively). It was also observed, higher antioxidant activity for the concentration of 1000 μg.mL-1 (89.76%). In the phytotoxicity assay was observed a dose dependent effect in the mitotic index and in the cellular events during cellular division. In this study it was possible to conclude that this species has allelochemical compounds which are able to interfere directly on the stabilization and development of other species.
Phytotoxicity of ethanolic extract of turnip leaves (Raphanus sativus L.)
Keywords: Allelopathy; Antioxidant; Development; Germination; Lettuce